How Learning Motivation Influences Feedback Experience and Preference in Chinese University EFL Students - Gan, Zhengdong (Frontiers in Psychology, 2020)
While there has been a large body of feedback research in the area of second language acquisition, the role of language learning motivation in the feedback process has rarely been researched. Drawing on the argument that students’ different learning behaviors, including their perceptions of and engagement with feedback, could have roots in learners’ fundamental motivational characteristics, this study intends to fill the gap by examining how second language learning motivational variables may predict EFL (English as a foreign language) students’ feedback experience and preference in order to promote feedback effectiveness. Results show that different components of the second language learning motivational construct appear to display differential associations with EFL students’ feedback experience and preference. Results also provide significant insights into a complex and dynamic view of how student preference for different types of feedback actually works in the feedback process. We therefore argue that teachers need to shoulder the burden of making the EFL classroom a supportive environment that promotes a positive self-concept and self-confidence as the first step towards stimulating students’ active feedback use, and that conditions need to be created to allow for connection of students’ preference for process-oriented feedback to action in order to maximize students’ pivotal role in the learning process.